La consolidación de una línea de investigación sobre trauma - González, Germán; Laverde, Laura Alicia; Forero P., Constanza; Agudelo G., Byron; Sepúlpeda D., Hernán Darío (Investigación y Educación en Enfermería, 2013)
.